2002
DOI: 10.1046/j.1532-5415.2002.50601.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Frailty in Community‐Dwelling Older Adults: Results of a Randomized, Controlled Trial

Abstract: Our results show that intensive ET can improve measures of physical function and preclinical disability in older adults who have impairments in physical performance and oxygen uptake and are not taking hormone replacement therapy better than a low-intensity home exercise program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
471
1
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(503 citation statements)
references
References 26 publications
17
471
1
14
Order By: Relevance
“…Lord et al (2003) found that 12 weeks of an intervention that included gait, balance, and weight-bearing exercises resulted in 22 % fewer falls in frail elderly individuals compared with control subjects. In addition, Binder et al (2002) showed significant improvements in balance and physical performance scores in the physically frail elderly after 36 weeks of multicomponent exercise intervention. In another study, Barnett et al (2003) demonstrated that 1 year of home-based strength, balance, and aerobic training resulted in increased balance and 40 % fewer falls in an exercise intervention group of elderly with physical frailty compared with a control group.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lord et al (2003) found that 12 weeks of an intervention that included gait, balance, and weight-bearing exercises resulted in 22 % fewer falls in frail elderly individuals compared with control subjects. In addition, Binder et al (2002) showed significant improvements in balance and physical performance scores in the physically frail elderly after 36 weeks of multicomponent exercise intervention. In another study, Barnett et al (2003) demonstrated that 1 year of home-based strength, balance, and aerobic training resulted in increased balance and 40 % fewer falls in an exercise intervention group of elderly with physical frailty compared with a control group.…”
Section: Discussionmentioning
confidence: 92%
“…This exercise intervention induced improvements in not only strength but also several parameters of functional capacity in the oldest old. Indeed, in younger frail elderly, multicomponent exercise programs appear to be the most effective intervention for improving the overall physical status of frail elderly individuals and prevent disability and other adverse outcomes (Binder et al 2002;Clemson et al 2012;Freiberger et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, people who have reached old age successfully are characterized by high levels of functioning in both physical and psychosocial domains (5)(6)(7). Several studies have shown that disability can be prevented or reduced by enhancing physical fitness through physical activity (8,9). In the psychological domain, one often focuses on specific age-related symptoms or disorders like memory impairment (10,11), depression (12) or dementia (13).…”
Section: Introductionmentioning
confidence: 99%
“…Binder et al 4 4 Mild to moderate frailty: Having two of the following criteria: 1) score between 18-32 on modified physical performance test; 2) difficulty or need for assistance on 2 or + IADLs and BADLs; 3) VO 2 peak between 10-18 mL/kg min.…”
Section: Muscle Strengtheningmentioning
confidence: 99%
“…Although there is no consensus on the definition of frailty, it is widely accepted as a multifactorial, clinical syndrome characterized by a state of physiological vulnerability resulting from a decrease in energy reserves and the ability to maintain or restore homeostasis after a destabilizing event 2,3 . Frailty syndrome is complex and involves declines in many physiological domains, including strength and muscle mass, flexibility, balance, coordination and cardiovascular function 4,5 , which generate high risk of falls, functional decline, hospitalization and death 6 . Frailty leads to the deterioration of quality of life, caregiver overload and high health care expenses 7 .…”
Section: Introductionmentioning
confidence: 99%